2017
DOI: 10.1111/aepr.12182
|View full text |Cite
|
Sign up to set email alerts
|

China's New Role in the International Financial Architecture

Abstract: The rise of China is challenging the international financial architecture in a number of ways. This paper highlights three that are of critical importance: the challenge of absorbing massive Chinese savings; the incorporation of China into a cohesive global financial safety net; and the organisation of China's participation in funding the demand for international investment projects. The global financial architecture needs to be reformed. But what role should China play? The paper defines the options open to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is instructive here to remember that Japan had previously sought to challenge Western development models, both in World War Two and (more peacefully) in the 1960s. Drysdale et al (, p. 259) find parallels between China's founding of the AIIB in 2016 and Japan's formation of the ADB fifty years earlier. Like the AIIB, the ADB was initially rejected by the United States, and although the United States did ultimately join this Japan‐led initiative, American support was lukewarm during the early years of its operations (McCawley, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is instructive here to remember that Japan had previously sought to challenge Western development models, both in World War Two and (more peacefully) in the 1960s. Drysdale et al (, p. 259) find parallels between China's founding of the AIIB in 2016 and Japan's formation of the ADB fifty years earlier. Like the AIIB, the ADB was initially rejected by the United States, and although the United States did ultimately join this Japan‐led initiative, American support was lukewarm during the early years of its operations (McCawley, ).…”
Section: Discussionmentioning
confidence: 99%
“…China has contributed to the framework for investment financing, but some authors question whether these institutions compete with or complement the existing framework (Drysdale et al 2017). Some media reported that the AIIB and the rest of initiatives have been launched to counterbalance or even "to rival" to the WB, the ADB and the IMF (Sudakov 2015; The BRICS bank: An acronym with capital 2014).…”
Section: Building a New International Financial Architecturementioning
confidence: 99%
“…Some academics doubt whether the PRC is creating an alternative or complementary institutional order (Beeson and Li 2016), but most of them defend that the PRC can work well with the established economic powers in reforming the existing architecture (Drysdale et al 2017). Some authors underline that the AIIB has followed international practices and was in favour of multilateralism in the setup of the AIIB, particularly after the unexpected decisions of several Western countries to participate in the initiative (Yang 2016).…”
Section: Building a New International Financial Architecturementioning
confidence: 99%
“…The inclusion of the RMB in the special drawing rights (SDR) basket will certainly help raise the profile of the RMB as a major international currency. Hence, it would have been useful if Drysdale et al (2017) had provided assessments of the future prospects for the RMB as a major international currency.…”
mentioning
confidence: 99%
“…Of course to achieve capital account openness significant domestic financial reforms are neededincluding the deleveraging of corporate debt, the improvement of local government finance, and major reforms of state-owned commercial banks and state-owned enterprises which are these banks' important loan clients-and China should focus on such reforms in this transition period. Drysdale et al (2017) should have discussed these critical issues.…”
mentioning
confidence: 99%